Depression with comorbid borderline personality disorder - could ketamine be a treatment catalyst? - Więdłocha, Magdalena; Marcinowicz, Piotr; Komarnicki, Jan; Tobiaszewska, Małgorzata; Dębowska, Weronika; Dębowska, Marta; Szulc, Agata (Frontiers in Psychiatry, 2024)
Borderline personality disorder (BPD) is diagnosed in 10-30% of patients with major depressive disorder (MDD), and the frequency of MDD among individuals with BPD reaches over 80%. The comorbidity of MDD and BPD is associated with more severe depressive symptoms and functional impairment, higher risk of treatment resistance and increased suicidality. The effectiveness of ketamine usage in treatment resistant depression (TRD) has been demonstrated in numerous studies. In most of these studies, individuals with BPD were not excluded, thus given the high co-occurrence of these disorders, it is possible that the beneficial effects of ketamine also extend to the subpopulation with comorbid TRD and BPD. However, no protocols were developed that would account for comorbidity. Moreover, psychotherapeutic interventions, which may be crucial for achieving a lasting therapeutic effect in TRD and BPD comorbidity, were not included. In the article, we discuss the results of a small number of existing studies and case reports on the use of ketamine in depressive disorders with comorbid BPD. We elucidate how, at the molecular and brain network levels, ketamine can impact the neurobiology and symptoms of BPD. Furthermore, we explore whether ketamine-induced neuroplasticity, augmented by psychotherapy, could be of use in alleviating core BPD-related symptoms such as emotional dysregulation, self-identity disturbances and self-harming behaviors. We also discuss the potential of ketamine-assisted psychotherapy (KAP) in BPD treatment. As there is no standard approach to the application of ketamine or KAP in individuals with comorbid TRD and BPD, we consider further research in the field as imperative. The priorities should include development of dedicated protocols, distinguishing subpopulations that may benefit most from such treatment and investigating factors that may influence its effectiveness and safety.